2016
DOI: 10.3390/molecules21081090
|View full text |Cite
|
Sign up to set email alerts
|

Order, Disorder, and Everything in Between

Abstract: In addition to the "traditional" proteins characterized by the unique crystal-like structures needed for unique functions, it is increasingly recognized that many proteins or protein regions (collectively known as intrinsically disordered proteins (IDPs) and intrinsically disordered protein regions (IDPRs)), being biologically active, do not have a specific 3D-structure in their unbound states under physiological conditions. There are also subtler categories of disorder, such as conditional (or dormant) disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 112 publications
(118 reference statements)
2
75
0
Order By: Relevance
“…In agreement with this, our bioinformatics analysis predicts structural elements in Lmod2, which are characterised by relatively large disorder probability, characteristic for intrinsically disordered protein regions (IDRs) (disorder probability > 0.5, Fig 2A) [3941]. Rattus norvegicus leiomodin2 contains three tryptophans (W73, W386 and W404), which are located in segments with high predicted disorder (Fig 2A).…”
Section: Resultssupporting
confidence: 64%
“…In agreement with this, our bioinformatics analysis predicts structural elements in Lmod2, which are characterised by relatively large disorder probability, characteristic for intrinsically disordered protein regions (IDRs) (disorder probability > 0.5, Fig 2A) [3941]. Rattus norvegicus leiomodin2 contains three tryptophans (W73, W386 and W404), which are located in segments with high predicted disorder (Fig 2A).…”
Section: Resultssupporting
confidence: 64%
“…Contrary to this deterministic interpretation, it is now well established that proteins need not always be folded to remain functional . A large fraction of the proteome across all three kingdoms is composed of intrinsically disordered proteins (IDPs) that, by definition, are ensembles of polymorphic conformers lacking rigid three‐dimensional structure . IDPs and segments within ordered proteins constituting intrinsically disordered regions (IDRs) are characterized by a combination of low mean hydrophobicity and relatively high net charge, important prerequisites for the absence of three‐dimensional structure in proteins under physiological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…It has been already shown that hub complexes are essential for any living organism and the deletion of a hub is fatal [95]. Besides, several IDPs involved in human pathogeneses are also hubs and examples of these disordered hubs with hundreds of protein partners are p53, α-synuclein, BRCA1, XPA, p21, p27, estrogen receptor and many others [93,94]. There are also IDPs capable of forming protein complexes known as "fuzzy" where they can adopt more than one conformation within the same partner, in a dynamic or static way [96,97].…”
Section: Cryptococcal Meningitismentioning
confidence: 99%
“…At this point is important to emphasize that to be an IDPs does not mean to be unfolded or to exist as an extended theoretical random coil. The IDP structure is not a random organization in solution and that is why only the term IDPs will be used in this thesis instead of other nomenclatures, such as intrinsically unfolded proteins, natively unfolded or even loopy [94] A great number of IDPs are well known to be structurally promiscuous, positioned at the center of the cell interactome, where they act as hubs for interactions with multiple protein partners [90]. The disordered-to-order transition is probably a unique characteristic of IDPs, allowing them to adapt to several different situations [90,93] and is what usually allow these hubs to be so promiscuous for the protein-protein interaction [93].…”
Section: Cryptococcal Meningitismentioning
confidence: 99%
See 1 more Smart Citation